Increased expression of cell adhesion molecule receptors on monocyte subsets in ischaemic heart failure - Wrigley, Benjamin J.; Shantsila, Eduard; Tapp, Luke D.; Gregory, Lip Y. H. (Thrombosis and Haemostasis, 2013)
The objective of this study was to evaluate the expression of cell adhesion molecule (CAM) receptors (integrins) on monocyte subsets in heart failure (HF) and examine their prognostic implication. Increased levels of soluble CAMs have been observed in patients with HF, but the precise mechanism of monocyte adhesion to the vascular endothelium remains unknown. Patients with acute HF (AHF, n=51) were compared to those with stable HF (SHF, n=42) and stable coronary artery disease (CAD, n=44) without HF. Expression of integrins-receptors to intercellular adhesion molecule-1 (ICAM-1R) and vascular CAM-1 (VCAM-1R) on monocyte subsets was assessed by flow cytometry. Monocyte subsets were defined as CD14++CD16–CCR2+ (‘classical’, Mon1), CD14++CD16+CCR2+ (‘intermediate’, Mon2), and CD14+CD16++CCR2– (‘non-classical’, Mon3). Compared to patients with SHF, those with AHF had significantly higher expression of ICAM-1R on Mon2 (p=0.01). Compared to those with stable CAD, patients with SHF had a significantly higher expression of ICAM-1R on Mon2 (p=0.025). Compared to SHF, patients with AHF had a similar expression of VCAM-1R on both Mon1 and Mon3 but significantly higher expression on Mon2 (p=0.019). There were no significant differences between SHF and CAD in monocyte expression of VCAM-1R. In multivariate Cox regression analysis, VCAM-1R expression on Mon2 was associated with adverse clinical outcome (death or rehospitalisation) in AHF [HR 1.07 (1.01–1.14), p=0.029]. In conclusion, HF is associated with increased monocyte expression of integrins-receptors to both ICAM-1 and VCAM-1, being particularly linked to Mon2 subset. Expression of VCAM-1R on Mon2 may have prognostic value in patients with AHF.
Keywords: Monocytes; monocyte subsets; heart failure; cell adhesion molecules